2008
DOI: 10.1080/13697130802178471
|View full text |Cite
|
Sign up to set email alerts
|

The role of quantitative ultrasound in predicting osteoporosis defined by dual-energy X-ray absorptiometry in pre- and postmenopausal women

Abstract: We concluded that, although DXA and QUS parameters were significantly correlated, QUS parameters cannot predict osteoporosis defined by DXA. Sensitivities and specificities of QUS parameters were not sufficiently high for QUS to be used as an alternative to DXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…There are many researchers who question the precision of peripheral bone mineral density measurements. Previous studies have reported that QUS parameters cannot be used to predict decreased BMD and that the sensitivities and specificities of QUS parameters are not sufficient to allow it to be used as an alternative to DXA [31-33], which is currently the gold standard for measuring BMD [34,35]. However, most psychiatric clinics do not have access to DXA equipment and DXA scanning is time consuming, costly and exposes patients to radiation, rendering it less than ideal for a large population survey.…”
Section: Discussionmentioning
confidence: 99%
“…There are many researchers who question the precision of peripheral bone mineral density measurements. Previous studies have reported that QUS parameters cannot be used to predict decreased BMD and that the sensitivities and specificities of QUS parameters are not sufficient to allow it to be used as an alternative to DXA [31-33], which is currently the gold standard for measuring BMD [34,35]. However, most psychiatric clinics do not have access to DXA equipment and DXA scanning is time consuming, costly and exposes patients to radiation, rendering it less than ideal for a large population survey.…”
Section: Discussionmentioning
confidence: 99%
“…A review of various clinical calcaneal QUS devices can be found elsewhere. 24,25 To examine the clinical utility of the calcaneal QUS system, Dane et al 26 and Trimpou et al 27 conducted studies on postmenopausal women that portrayed a moderate association of both BUA and SOS on the aBMD of the lumbar spine and femur, as assessed by DXA. In the case of premenopausal women, SOS was seen to be significantly correlated to aBMD at the lumbar spine and femur.…”
Section: Introductionmentioning
confidence: 99%
“…The BMD measurement is accepted by the WHO as the gold standard for the diagnosis of osteoporosis. In another study, we have found a poor to moderate correlation between Quantitative ultrasound parameters (BUA, SOS, SI) and femoral and spinal BMD in pre and postmenopausal women (5). Tuna et al also reported, that the diagnostic value of tibial SOS did not seem to be high for discriminating between normal and low BMD at the femur and lumbar spine in postmenopausal women (6).…”
mentioning
confidence: 78%